A covalent organic framework composite membrane for efficient lithium extraction and its preparation method and application

By introducing specific compounds and flexible substrate materials in the preparation process of covalent organic frame composite film, the problem of poor selective separation of lithium ions in the prior art is solved, and efficient and selective lithium ion extraction is achieved.

CN119034503BActive Publication Date: 2025-04-15GUANGDONG MECHANICAL & ELECTRICAL COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411078032.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2025-04-15
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

When the existing nanofiltration membrane and selective ion exchange membrane extract lithium from salt lakes and seawater, it is difficult to achieve selective separation of Li+/K+ and Li+/Na+, and the monovalent ions in the brine will compete for lithium ions, affecting the separation effect.

Method used

By introducing triaminoguanidine hydrochloride and 4,4'-diaminodiphenyl ether in the preparation of the covalent organic frame, combining flexible substrate materials and specific reaction conditions, a covalent organic frame composite film with efficient lithium extraction was prepared.

Benefits of technology

It realizes efficient selective transmission of lithium ions, significantly improves the separation performance of lithium ions, reduces the transmission of divalent ions, and improves the transmission efficiency of lithium ions through reversible coordination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119034503B_ABST
    Figure CN119034503B_ABST
Patent Text Reader

Abstract

The present invention discloses a covalent organic framework composite membrane for efficient lithium extraction, a preparation method and an application. The covalent organic framework composite membrane for efficient lithium extraction is mainly prepared by the reaction of triaminoguanidine hydrochloride, 4,4'-diaminodiphenyl ether and 2,4,6-triformylphloroglucinol. The present invention effectively improves the adsorption activity of the covalent organic framework skeleton to lithium ions by introducing triaminoguanidine hydrochloride and 4,4'-diaminodiphenyl ether in the process of synthesizing the covalent organic framework. Due to the electrostatic repulsion, the covalent organic framework composite membrane shows superiority in the transmission of monovalent ions, while reducing the transmission of divalent ions. In addition, the introduced ether functional group can form a reversible coordination effect with lithium ions, further improving the transmission efficiency of lithium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite membrane, and in particular to a covalent organic framework composite membrane for efficient lithium extraction, a preparation method and an application thereof. Background Art

[0002] As the metal element with the lightest atomic weight and the lowest standard electrode potential in nature, lithium is the most ideal battery material and is known as the "white oil" of the future. With the rapid development of new energy vehicles, energy storage and other fields, the demand for lithium resources is also growing rapidly worldwide.

[0003] Existing membrane technologies such as nanofiltration membranes and selective ion exchange membranes are used to extract lithium from salt lakes and seawater (Membranes, 2020, 10(8):168; Desalination, 2015, 359:59-63.). These membranes are not suitable for Li + / Mg 2+ The selectivity is high, but it is difficult to achieve Li + / K + , Li + / Na + Selective separation. The monovalent ions in the brine will also compete with lithium ions, affecting the lithium ion separation effect in the membrane separation process. It is still difficult to achieve accurate and efficient separation of lithium ions. Therefore, the development of new membrane materials with lithium ion-specific separation function is the main development direction of lithium extraction technology in seawater in the future.

[0004] In recent years, as a new type of material, two-dimensional covalent organic frameworks (COFs) have been developed with the design flexibility to allow customization of different pore sizes and adsorption active sites within the pores, providing great potential for COFs in a variety of specific applications (Chemical Society Reviews, 2020, 49(17): 6248-6272.). However, the application of COFs in the adsorption and extraction of lithium from liquid lithium resources such as salt lakes and seawater has not been fully developed. Therefore, it is necessary to explore the improvement of COFs materials through surface modification technology and finely control their nanochannel structure and charge state, which will significantly improve the lithium ion selective membrane materials for Li in the separation of monovalent and divalent ions. + The selectivity is of great significance. Summary of the invention

[0005] One of the purposes of the present invention is to provide a covalent organic framework composite membrane for efficient lithium extraction, the preparation method of which is simple and controllable, can effectively and selectively permeate lithium ions, and has high separation performance to overcome the shortcomings of the prior art.

[0006] The invention also provides a covalent organic framework composite membrane for efficient lithium extraction, which is prepared by the reaction of triaminoguanidine hydrochloride, 4,4'-diaminodiphenyl ether and 2,4,6-triformylphloroglucinol.

[0007] The second object of the present invention is to provide a method for preparing the above-mentioned covalent organic framework composite membrane for efficient lithium extraction.

[0008] The present invention provides the following technical solutions:

[0009] The method for preparing a covalent organic framework composite membrane for efficient lithium extraction comprises the following steps:

[0010] (1) In a sealed container, triaminoguanidine hydrochloride and 4,4'-diaminodiphenyl ether are added in sequence, and stirred and dissolved with an aqueous mixed solvent to obtain a mixed solution A.

[0011] (2) 2,4,6-triformylphloroglucinol is added to a sealed container, mixed with an organic solvent, and stirred to dissolve to obtain a mixed solution B.

[0012] (3) The mixed solution A and the mixed solution B are transferred to the two sides of the reaction tank respectively, and a flexible substrate material is placed at the connection point. The reaction is carried out in a closed environment. After the reaction is completed, the covalent organic framework composite film material is obtained after washing and drying.

[0013] The aqueous mixed solvent described in step (1) comprises acetic acid and deionized water in a volume ratio of 1:4.83, and the acetic acid with a purity greater than or equal to 99.7% is preferred.

[0014] The molar concentration ratio of triaminoguanidine hydrochloride to 4,4'-diaminodiphenyl ether in step (1) is 0.4:1 to 1.3:1, preferably 1:1.

[0015] The amount of 2,4,6-triformyl phloroglucinol added in step (2) is calculated according to the sum of the amounts of triaminoguanidine hydrochloride and 4,4'-diaminodiphenyl ether added in step (1). The molar concentration ratio of 2,4,6-triformyl phloroglucinol to the sum of the molar concentrations of triaminoguanidine hydrochloride and 4,4'-diaminodiphenyl ether in step (1) is 1:0.5-1:2, preferably a molar concentration ratio of 1:1.

[0016] The organic solvent described in step (2) includes a mixed solution of ethyl acetate and 1,3,5-trimethylbenzene, wherein the volume ratio of ethyl acetate to 1,3,5-trimethylbenzene is 1:4.83, and preferably ethyl acetate with a purity greater than or equal to 99.5% and 1,3,5-trimethylbenzene with a purity greater than or equal to 99.5%.

[0017] The stirring conditions in steps (1) and (2) are preferably: stirring at 20-40° C. for 24 h and a rotation speed of 300-600 rpm.

[0018] The volume of the mixed solution A and the mixed solution B transferred in step (3) is 5-30 ml, preferably 10 ml.

[0019] The reaction tank described in step (3) is an H-shaped reaction tank made of glass, and its through hole area is 7.068cm 2 .

[0020] The flexible substrate material in step (3) includes polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, or lithium titanium aluminum phosphate (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) mixed polymer membrane material. Preferably containing lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) mixed polymer membrane material. Containing lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7 The mixed polymer membrane material of (PO4)3) is lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7 Mixed polymer membrane material of (PO4)3) and polyacrylonitrile or polyvinylidene fluoride-hexafluoropropylene.

[0021] The reaction conditions described in step (3) are: 25-80°C for 48-96h; preferably 60°C for 72h.

[0022] The washing solvents described in step (3) are ethanol, methanol and water in sequence.

[0023] The drying conditions described in step (3) are: drying at 30-60° C. for 10-36 h under a vacuum environment; preferably drying at 50° C. for 24 h.

[0024] The third object of the present invention is to provide the application of the above-mentioned covalent organic framework composite membrane.

[0025] Specifically, it involves the application of covalent organic framework composite membranes in lithium extraction.

[0026] Advantages of the present invention:

[0027] The present invention effectively improves the adsorption activity of the covalent organic framework skeleton to lithium ions by introducing triaminoguanidine hydrochloride and 4,4'-diaminodiphenyl ether in the process of synthesizing the covalent organic framework. Due to the electrostatic repulsion, the covalent organic framework composite membrane shows superiority in the transmission of monovalent ions while reducing the transmission of divalent ions. In addition, the introduced ether functional group can form a reversible coordination effect with lithium ions, further improving the transmission efficiency of lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of the lithium ion extraction principle implemented in the test of the present invention.

[0029] Figure 2 Li of the covalent organic framework composite film of Examples 1-3 of the present invention + Permeation flux comparison chart.

[0030] Figure 3 (a) is a nitrogen adsorption-desorption isotherm graph and (b) is a pore size distribution graph of the covalent organic framework composite film of Example 1 of the present invention.

[0031] Figure 4 This is an infrared spectrum of the covalent organic framework composite film of Example 1 of the present invention.

[0032] Figure 5 The current density-time curves of the covalent organic framework composite films of Examples 1-3 of the present invention. DETAILED DESCRIPTION

[0033] The present invention is further explained below with reference to the examples, but the examples do not limit the present invention in any form.

[0034] Example 1

[0035] (1) Preparation process of ionic liquids based on water-based mixed solvents

[0036] 2.4 ml of acetic acid (purity ≥ 99.7%) and 11.6 ml of deionized water were measured and mixed into a sealed container to form a water-based mixed solvent. Then 14.4914 mg of triaminoguanidine hydrochloride and 20.4314 mg of 4,4'-diaminodiphenyl ether were added to the mixed solvent in sequence. Stirred at 25°C for 24 hours at a speed of 400 rpm to obtain a mixed solution A, which is an ionic liquid.

[0037] (1) Preparation process of ionic liquids based on organic mixed solvents

[0038] 2.4 ml of ethyl acetate (purity ≥ 99.5%) and 11.6 ml of 1,3,5-trimethylbenzene (purity ≥ 99.5%) were measured and mixed into a sealed container to form an organic mixed solvent. Then 42 mg of 2,4,6-triformylphloroglucinol was added to the mixed solvent. Stir at 25°C for 24 hours at a speed of 400 rpm to obtain a mixed solution B, which is an ionic liquid.

[0039] (2) Preparation process of covalent organic framework

[0040] A base material containing lithium aluminum titanium phosphate (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) mixed polymer flexible substrate material, the internal space of the H-type reaction tank is divided into two solution tanks on the left and right. Take 10 ml of the mixed solution A of step (1) and the mixed solution B of step (2) and transfer them to the solution tanks on both sides of the substrate material of the H-type reaction tank, react at 60°C for 72 hours, and the mixed solution A and the mixed solution B slowly penetrate, and then form a covalent organic framework (COF) material on one side of the substrate material. After washing with ethanol, methanol and water in turn, put it into a vacuum drying oven and dry it at 50°C for 24 hours to obtain a covalent organic framework composite film 1.

[0041] The covalent organic framework composite film 1 is used as a lithium ion extraction device (see Figure 1 ) as a separator for extracting and separating lithium ions. The lithium ion extraction device is made of 3mm thick acrylic plate and silicone sheet, with an outer size of 3*3cm square, leaving 1cm in the middle 2 The square is used as the active center area. The cathode compartment, seawater compartment, and anode compartment are separated by an anion exchange membrane (AEM) and a covalent organic framework composite film 1. The cathode compartment uses Pt / C as the electrode and 3 mL of deionized water as the cathode electrolyte; the seawater compartment uses 500 ml of diluted seawater as the lithium source liquid; the anode compartment uses RuO2 as the electrode and 8 mL of 0.1 M Na2SO4 as the anode electrolyte. The three chambers are pumped by a peristaltic pump at 3 mL min -1 The voltage applied to both ends of the electrode was constant at 2V, the ambient temperature was 25°C, and the lithium extraction time was 12.5h. The permeation flux of lithium ions was 3.945mmol·m -2 ·h -1 Compared with commercial cation membranes (CEM), it has a + and K + The selectivity of cations reached 23137.510 and 245.521, respectively, which is significantly higher than the 14.351 and 0.750 of commercial membranes (see Figure 2 ).

[0042] Fourier transform infrared spectrometer, specific surface area and porosity analyzer were used to characterize and analyze the materials. Figure 3 The nitrogen adsorption-desorption isotherm (a) and pore size distribution (b) show that the BET surface area of ​​the covalent organic framework composite film 1 is 62.556 m 2 ·g -1 , the center of the pore size distribution is 3.23nm. Figure 4 Infrared spectrum of 1608cm -1 and 1585cm -1 The stretching vibration peaks of C=N and C=C appeared respectively, indicating that the two monomers successfully underwent condensation reaction with 1,3,5-trimethylbenzene. In addition, no amine (NH~3320cm -1 and 3220cm -1 ) and aldehyde (C=O~1645cm -1 ) stretching signal, indicating that there is no unreacted monomer. Figure 5 In the current density-time curve, the covalent organic framework composite film 1 shows a lower current density than the commercial CEM, which means that the covalent organic framework composite film 1 can effectively prevent the entry of other impurity ions, which is consistent with Figure 2 The results are consistent.

[0043] Example 2

[0044] (1) Preparation process of ionic liquids based on water-based mixed solvents

[0045] 2.4 ml of acetic acid (purity ≥ 99.7%) and 12 ml of deionized water were measured and mixed into a sealed container to form a water-based mixed solvent. Then 19.6812 mg of triaminoguanidine hydrochloride and 12.0144 mg of 4,4'-diaminodiphenyl ether were added to the mixed solvent in sequence. Stirred at 25°C for 24 hours at a speed of 400 rpm to obtain a mixed solution A, which is an ionic liquid.

[0046] (2) Preparation process of ionic liquids based on organic mixed solvents

[0047] 2.4 ml of ethyl acetate (purity ≥ 99.5%) and 12 ml of 1,3,5-trimethylbenzene (purity ≥ 99.5%) were measured and mixed into a sealed container to form an organic mixed solvent. Then 42 mg of 2,4,6-triformylphloroglucinol was added to the mixed solvent. Stir at 25°C for 24 hours at a speed of 400 rpm to obtain a mixed solution B, which is an ionic liquid.

[0048] (3) Preparation process of covalent organic framework

[0049] Take 20 ml of the mixed solution A of step (1) and the mixed solution B of step (2) and transfer them to the two sides of the glass H-type reaction tank, put a glass fiber flexible substrate material in the middle connection, and react at 60°C for 72 hours. After washing with ethanol, methanol and water, put it in a vacuum drying oven at 40°C for 50 hours to obtain a covalent organic framework composite film 2.

[0050] The covalent organic framework composite film 2 is used as a separator in a lithium ion extraction device to extract and separate lithium ions. The test conditions are consistent with those of Example 1, and the Li + The permeation flux is 2.128mmol·m -2 ·h -1 , for Na + and K + The selectivities of cations reached 1614.707 and 22.160 respectively.

[0051] Example 3

[0052] (1) Preparation process of ionic liquids based on water-based mixed solvents

[0053] 2.4 ml of acetic acid (purity ≥ 99.7%) and 11.6 ml of deionized water were measured and mixed into a sealed container to form a water-based mixed solvent. Then 12.6522 mg of triaminoguanidine hydrochloride and 22.0264 mg of 4,4'-diaminodiphenyl ether were added to the mixed solvent in sequence. Stirred at 25°C for 24 hours at a speed of 400 rpm to obtain a mixed solution A, which is an ionic liquid.

[0054] (2) Preparation process of ionic liquids based on organic mixed solvents

[0055] 2.4 ml of ethyl acetate (purity ≥ 99.5%) and 11.6 ml of 1,3,5-trimethylbenzene (purity ≥ 99.5%) were measured and mixed into a sealed container to form an organic mixed solvent. Then 42 mg of 2,4,6-triformylphloroglucinol was added to the mixed solvent. Stir at 25°C for 24 hours at a speed of 400 rpm to obtain a mixed solution B, which is an ionic liquid.

[0056] (3) Preparation process of covalent organic framework

[0057] Take 20 ml of the mixed solution A of step (1) and the mixed solution B of step (2) and transfer them to the two sides of the glass H-type reaction tank, put the polyacrylonitrile flexible substrate material in the middle connection, and react at 30°C for 80 hours. After washing with ethanol, methanol and water, put it in a vacuum drying oven at 50°C for 24 hours to obtain a covalent organic framework composite film 3.

[0058] The covalent organic framework composite film 3 was used as a separator in a lithium ion extraction device to extract and separate lithium ions. The test conditions were consistent with those in Example 1, and the Li + The permeation flux was 2.029mmol·m -2 ·h -1 , for Na + and K + The selectivities of cations reached 3327.283 and 43.934 respectively.

[0059] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A covalent organic framework composite membrane for efficient lithium extraction, characterized in that: It is mainly prepared by the reaction of triaminoguanidine hydrochloride, 4,4'-diaminodiphenyl ether and 2,4,6-triformylphloroglucinol; its preparation method is as follows: The following steps are involved: (1) adding triaminoguanidine hydrochloride and 4,4'-diaminodiphenyl ether in sequence into a sealed container, stirring and dissolving with a mixed solvent of an aqueous system to obtain a mixed solution A; the mixed solvent of the aqueous system comprises acetic acid and deionized water, the volume ratio of the acetic acid to the deionized water is 1:4.83; the molar concentration ratio of the triaminoguanidine hydrochloride to the 4,4'-diaminodiphenyl ether is 0.4:1-1.3:1; (2) adding 2,4,6-triformylphloroglucinol to a sealed container, mixing with an organic solvent, stirring to dissolve, and obtaining a mixed solution B; wherein the molar concentration ratio of the 2,4,6-triformylphloroglucinol to the molar concentration ratio of the triaminoguanidine hydrochloride and the 4,4'-diaminodiphenyl ether in step (1) is 1:0.5-1:2; (3) The flexible substrate material is vertically arranged in the middle of the reaction tank, and the reaction tank is divided into two parts. The mixed solution A and the mixed solution B are respectively transferred to the tanks on both sides of the flexible substrate material to react in a closed environment. After the reaction is completed, the covalent organic framework composite thin film material is obtained after washing and drying. The volumes of the transferred mixed solution A and mixed solution B are 5-30 ml respectively. The reaction tank is an H-type reaction tank made of glass, and its through hole area is 7.068 cm 2 The reaction conditions are: 25-80℃ for 48-96h; the washing solvent sequence is ethanol, methanol, and water; the drying conditions are: drying at 30-60℃ for 10-36h under vacuum.

2. The covalent organic framework composite membrane for efficient lithium extraction according to claim 1, characterized in that: In the steps (1) and (2), the stirring conditions are: stirring at 20-40° C. for 24 hours and a rotation speed of 300-600 rpm.

3. The method for preparing the covalent organic framework composite membrane for efficient lithium extraction according to claim 1, characterized in that: The following steps are involved: (1) adding triaminoguanidine hydrochloride and 4,4'-diaminodiphenyl ether in sequence into a sealed container, stirring and dissolving with a mixed solvent of an aqueous system to obtain a mixed solution A; the mixed solvent of the aqueous system comprises acetic acid and deionized water, the volume ratio of the acetic acid to the deionized water is 1:4.83; the molar concentration ratio of the triaminoguanidine hydrochloride to the 4,4'-diaminodiphenyl ether is 0.4:1-1.3:1; (2) adding 2,4,6-triformylphloroglucinol to a sealed container, mixing with an organic solvent, stirring to dissolve, and obtaining a mixed solution B; wherein the molar concentration ratio of the 2,4,6-triformylphloroglucinol to the molar concentration ratio of the triaminoguanidine hydrochloride and the 4,4'-diaminodiphenyl ether in step (1) is 1:0.5-1:2; (3) The flexible substrate material is vertically arranged in the middle of the reaction tank, and the reaction tank is divided into two parts. The mixed solution A and the mixed solution B are respectively transferred to the tanks on both sides of the flexible substrate material to react in a closed environment. After the reaction is completed, the covalent organic framework composite thin film material is obtained after washing and drying. The volumes of the transferred mixed solution A and mixed solution B are 5-30 ml respectively. The reaction tank is an H-type reaction tank made of glass, and its through hole area is 7.068 cm 2 ; The reaction conditions are: 25-80℃ for 48-96h; the washing solvent sequence is ethanol, methanol, water; the drying conditions are: 30-60℃ for 10-36h under vacuum; 4. The method for preparing a covalent organic framework composite membrane for efficient lithium extraction according to claim 3, characterized in that: In the steps (1) and (2), the stirring conditions are: stirring at 20-40° C. for 24 hours and a rotation speed of 300-600 rpm.

5. The method for preparing a covalent organic framework composite membrane for efficient lithium extraction according to claim 3, characterized in that: In the step (3), the flexible substrate material includes polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene or a mixed polymer film material containing lithium titanium aluminum phosphate.

6. The method for preparing a covalent organic framework composite membrane for efficient lithium extraction according to claim 3, characterized in that: The mixed polymer membrane material containing lithium titanium aluminum phosphate is a mixed polymer membrane material of lithium titanium aluminum phosphate and polyacrylonitrile or polyvinylidene fluoride-hexafluoropropylene.

7. Use of the covalent organic framework composite membrane according to claim 1 in lithium extraction.

Citation Information

Patent Citations

  • Preparation and application method of selective electrodialysis ion separation membrane

    CN116116252A

  • Tailored covalent organic framework membranes for lithium extraction and recycling

    WO2023073669A1